Effects of dispersed copper nanoparticles on Ni-ceria based dry methanol fuelled low temperature solid oxide fuel cells. Issue 11 (21st February 2019) - Jeon, Ok Sung; Lee, Jin Goo; Ji, Yunseong; Lee, Sung-hun; Kwon, Ohchan; Kim, Jeong Pil; Shul, Yong Gun
Abstract : Copper impregnation was selected to decrease the carbon deposition and enhance the performance at low temperature of dry methanol fuelled low temperature solid oxide fuel cells. Abstract : Methanol is an attractive energy source due to its portability and thermodynamic coke resistance by its oxygen content. In order to operate dry methanol fuel low temperature solid oxide fuel cells (LT-SOFCs), it is important to solve the problems of carbon formation and its low performance. In this study, copper impregnation was selected to decrease the carbon deposition and enhance the performance at low temperature. The interaction of copper, ceria and nickel improves CO oxidation capacity which improves coke tolerance and nano-sized nickel copper alloys improved durability and catalytic performance under methanol feed. It markedly amplified the performance about 0.4 W cm −2 at 550 °C with the durable operation at 1.4 A cm −2 over 50 h. Loading copper nanoparticles is promising method for Ni-ceria based LT-SOFC using methanol fuel with high performance and stable operation.